FAILURE ANALYSIS OF THE FLAT CHAIN OF SCRAPER CONVEYOR - ZHAI JianHua; ZHANG WanLin; WANG QianBao; WEI XiaoHua; SHEN Cheng; LIU ZhiJie (Jixie qiangdu)
As one of the key transmitting components and wearing parts of scraper conveyor,There are different types of wear which result to the failure of flat type chains. This study focused on the failure of the flat chains of Joy scraper conveyor used in Shendong Coal Mining Group. 3 D scanner was used to acquire the surface details of both worn and unworn flat chains. The data were then used to reconstruct the solid 3 D models of these two parts. Software package CATIA was employed to compare the models,including the wear volumes,positions and quantitative analysis of wear. The results showed that wear is the main failure mode of flat chain,but flat ring and ring have different Wear and wear positions. It provides a reference for people who engaged in mining machinery for failure analysis and laser repair wear flat chain.